Living in ancestrally diverse states of the United States is associated with greater vagal tone - Harrod, Ethan G.; Shrira, Ilan; Martin, Jared D.; Niedenthal, Paula M. (Frontiers in Psychology, 2023)
Historically, exposure to dissimilar others (“strangers”) was a physiologically arousing event – resulting in avoidance, distrust, and even conflict. Despite this, contemporary migration patterns are increasing intergroup contact. What gives rise to an individual’s ability to regulate their arousal such that social engagement with outgroup members is possible? We propose that cultural practices that evolve in ancestrally diverse, compared to ancestrally homogeneous, societies provide more opportunities for society members to engage in emotion regulation. This regulatory exercise in turn promotes higher vagal tone – a physiological indicator of one’s ability to effectively manage arousal in social interaction. In a secondary analysis of data from the MIDUS 2 Biomarker Project we find that the ancestral diversity of the states of the United States significantly predicts the average vagal tone of the state’s citizens. The findings suggest that social context is associated with predictable and significant adaptations of human physiology over individual lifetimes.